2018
DOI: 10.1002/adma.201804470
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile and Programmable Photodoping in MoTe2 for Photoresist‐Free Complementary Electronic Devices

Abstract: 2D transition‐metal dichalcogenide (TMD)‐based electronic devices have been extensively explored toward the post‐Moore era. Huge efforts have been devoted to modulating the doping profile of TMDs to achieve 2D p–n junctions and inverters, the fundamental units in logic circuits. Here, photoinduced nonvolatile and programmable electron doping in MoTe2 based on a heterostructure of MoTe2 and hexagonal boron nitride (BN) is reported. The electron transport property in the MoTe2 device can be precisely controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
82
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 36 publications
1
82
0
1
Order By: Relevance
“…The transfer curves ( I sd – V g ) of MoS 2 , MoTe 2 , and vdWHs under high vacuum (10 −7 mbar) are shown in Figure d. The pristine MoTe 2 device shows a typical hole‐dominated ambipolar transport behavior and the MoS 2 transistor exhibits electron transport characteristics, consistent with previous reports . The pristine transfer characteristics of vdWHs shows anti‐ambipolar transport behavior ascribed to the recombination of the free holes in MoTe 2 and the free electrons in MoS 2 , which further verifies the type II band alignment in this pristine heterostructure device .…”
supporting
confidence: 88%
“…The transfer curves ( I sd – V g ) of MoS 2 , MoTe 2 , and vdWHs under high vacuum (10 −7 mbar) are shown in Figure d. The pristine MoTe 2 device shows a typical hole‐dominated ambipolar transport behavior and the MoS 2 transistor exhibits electron transport characteristics, consistent with previous reports . The pristine transfer characteristics of vdWHs shows anti‐ambipolar transport behavior ascribed to the recombination of the free holes in MoTe 2 and the free electrons in MoS 2 , which further verifies the type II band alignment in this pristine heterostructure device .…”
supporting
confidence: 88%
“…Lim et al exploited atomic‐layer‐deposition‐generated H‐doping to achieve electron‐dominated α‐MoTe 2 flake with electron mobility of 18 cm 2 V −1 s −1 , which finally gave rise to stable CMOS inverters with large gain value (29) and small static power dissipation on the order of nanowatts . Very recently, by combining MoTe 2 with BN and forming a heterostructure between them, Liu et al proposed a photodoping method to accurately adjust the electron conduction characteristics (concentration and mobility of electrons) of MoTe 2 FET via tuning the amplitude of the applied photodoping gate . It was found that the induced photodoping effect was repeatable and nonvolatile and could be maintained for more than 14 days without ambient stimulation.…”
Section: Functional Applications Of Ambipolar Transistorsmentioning
confidence: 99%
“…c) The obtained voltage gain values of the MoTe 2 inverter under different input biases. It is found that the maximum gain value increases from 18, 42, to 98 when V DD augments from 1, 2 to 3 V. Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Functional Applications Of Ambipolar Transistorsmentioning
confidence: 99%
“…Photodetectors, converting light into electrical signal, demonstrate a wide range of applications in our daily lives, including optical telecommunications, remote sensing, video imaging, motion detection, and so forth . 2D layered materials have been rapidly established as promising building blocks for state‐of‐the‐art photodetectors, owing to their unique crystal structure and optical/electrical properties . 2D materials possess a layered structure, in which the atoms within each layer are covalently bonded, while different layers are held together by van der Waals interactions.…”
Section: Introductionmentioning
confidence: 99%